Achieving the Proposed Targets in the European Union for the Sustainable Development Goal - Affordable and Clean Energy - Carmen Valentina RĂDULESCU; Florina BRAN; Florin DOBRE; Dumitru Alexandru BODISLAV; Sorin Petrică ANGHELUȚĂ (Communications of International Proceedings, 2021)
Mitigation of the effects of climate change can be achieved through the use of resources and technologies that take into account the possibility of renewable energy production. Pollution and health are areas that can be included in the priority list of local communities. Adapting to climate change, as well as mitigating its effects, is based on resource efficiency. Technological innovations in the field of renewable energy lead to an easier energy transition. Objective 7 of sustainable development - Affordable and clean energy pursues these aspects. The article examines the progress made in achieving the targets proposed by the Member States of the European Union. The elimination of fossil fuels from their use in the production of electricity can be done gradually, by replacing them with renewable resources. Green and sustainable energy solutions can meet the challenges of meeting high energy demands.
Keywords: European Union; energy; renewable resources